3,4-diidroquinazolin-4-onas e 1H-benzo[d]imidazóis : planejamento utilizando hibridação molecular, síntese e atividade inibitória sobre o crescimento de Mycobacterium tuberculosis - Macchi, Fernanda Souza (2017)
Using the classical hybridization approach series of 1H-benzo[d]imidazoles and 3,4-dihydroquinazolin-4-ones were synthesized and evaluated as inhibitors of Mycobacterium tuberculosis growth. Chemical modifications and structure-activity relationship studies yielding potent antitubercular agents with minimum inhibitory concentration values in submicromolar range. Further, the synthesized compounds were active against drug-resistant strains and were devoid of apparent toxicity to HepG2, HaCat, and Vero cells. In addition, some 3,4-dihydroquinazolin-4-ones showed low risk of cardiac toxicity, no signals of neurotoxicity or morphological alteration in zebrafish (Danio rerio) models. Therefore, these data denote that this class of molecules may furnish candidates for future development of novel anti-TB drug alternatives.